Membangun Semangat Nasionalisme Mahasiswa Melalui Pendidikan Kewarganegaraan - Isna Nadifah Nur Fauziah; Dinie Anggraeni Dewi (Civiliza Publishing, 2021)
This study aims to determine the nature of nationalism in students through civic education. The research method uses a qualitative approach with literature study methods from reliable sources. Citizenship education aims to create citizens who have iansight into nationality, instill a sense of love for the country, and feel proud to be Indonesian citizens in the nation's future youth, including students. With the development of technology in the era of globalization, it has demanded high morality and understanding of nationalism. To add to the spirit of nationalism among the younger generation, especially students, namely mentality development, redefinition of the understanding and implementation of the values ​​of nationalism.